Diluar Ilmu Pengetahuan: Eksplorasi Kecemasan Masyarakat Victoria dalam The Strange Case of Dr. Jekyll and Mr. Hyde - Yusra, Shabrina Adzani (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This study examines how Robert Louis Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde reflects Victorian anxieties surrounding misuse of scientific discoveries. The novels follow Dr. Henry Jekyll, a respected physician who creates a potion to unleash his darker self in the form of the monstrous Edward Hyde. Using a historical-biographical approach and qualitative analysis, this study draws on primary data from novels supported by secondary sources including literary criticism and journal articles. The findings reveal that Stevenson addresses Victorian fears of unchecked scientific progress through Dr. Jekyll’s experiments, the societal reactions to Mr. Hyde and the depiction of Jekyll’s hubris, which ultimately highlight the era’s concerns about the ethical limits of science.